Atorvastatin favorably modulates a clinical hepatocellular carcinoma risk gene signature. Issue 9 (16th June 2022) - Kim, Myung‐Ho; Kim, Mi‐Young; Salloum, Shadi; Qian, Tongqi; Wong, Lai Ping; Xu, Min; Lee, Yoojin; Shroff, Stuti G.; Sadreyev, Ruslan I.; Corey, Kathleen E.; Baumert, Thomas F.; Hoshida, Yujin; et al.
Abstract: Lipophilic but not hydrophilic statins have been shown to be associated with reduced risk for hepatocellular carcinoma (HCC) in patients with chronic viral hepatitis. We investigated differential actions of lipophilic and hydrophilic statins and their ability to modulate a clinical prognostic liver signature (PLS) predicting HCC risk in patients with liver disease. Hepatitis C virus (HCV)–infected Huh7.5.1 cells, recently developed as a model to screen HCC chemopreventive agents, were treated with lipophilic statins (atorvastatin and simvastatin) and hydrophilic statins (rosuvastatin and pravastatin), and then analyzed by RNA sequencing and PLS. Lipophilic statins, particularly atorvastatin, more significantly suppressed the HCV‐induced high‐risk pattern of PLS and genes in YAP and AKT pathway implicated in fibrogenesis and carcinogenesis, compared with the hydrophilic statins. While atorvastatin inhibited YAP activation through the mevalonate pathway, the distinctive AKT inhibition of atorvastatin was mediated by stabilizing truncated retinoid X receptor alpha, which has been known to enhance AKT activation, representing a target for HCC chemoprevention. In addition, atorvastatin modulated the high‐risk PLS in an in vitro model of nonalcoholic fatty liver disease (NAFLD). Conclusion : Atorvastatin distinctively inhibits YAP and AKT activation, which are biologically implicated in HCC development, and attenuates a high‐risk PLS in an in vitro model of HCV infection and NAFLD. These findings suggest that atorvastatin is the most potent statin to reduce HCC risk in patients with viral and metabolic liver diseases. Abstract : Atorvastatin suppresses HCC risk gene signature through modulation of YAP/AKT/metallothionein pathways.image